(untitled) (Kairaranga, 2017)
Student agency is a hot topic in education in New Zealand at the moment. Future-focused learning and innovative learning environments seem to focus on student agency, but what does ‘agency’ actually mean? What does it look like for gifted students? And how do teachers to develop it in their students? In response to these questions, this position paper reviews the concept of student agency from an empirical base, asserts that curricula can be used to develop and support student agency, then looks at one example of a specialist curriculum for gifted learners that intentionally supports student agency.